Associations of pathogen‐specific and host‐specific characteristics with disease outcome in patients with Staphylococcus aureus bacteremic pneumonia. Issue 7 (19th July 2019) - Sharma‐Kuinkel, Batu K; Tkaczyk, Christine; Bonnell, Jessica; Yu, Li; Tovchigrechko, Andrey; Tabor, David E; Park, Lawrence P; Ruffin, Felicia; Esser, Mark T; Sellman, Bret R; Fowler, Vance G; Ruzin, Alexey
Abstract: Objective: To understand the relationships of Staphylococcus aureus (SA) bacteremic pneumonia (SABP) outcome with patient‐specific and SA‐specific variables. Methods: We analysed SA bloodstream isolates and matching sera in SABP patients by sequencing SA isolates ( n = 50) and measuring in vitro AT production, haemolytic activity and expression of ClfA and ClfB. Controls were sera from gram‐negative bacteremia patients with or without pneumonia and uninfected subjects. Levels of IgGs, IgMs and neutralizing antibodies (NAbs) against SA antigens were quantified and analysed by one‐way ANOVA. Associations of patient outcomes with patient variables, antibody levels and isolate characteristics were evaluated by univariate and multivariate logistic regression analyses. Results: SABP patients had higher levels of IgGs against eight virulence factors and anti‐alpha toxin (AT) NAbs than uninfected controls. Levels of IgG against AT and IgMs against ClfA, FnbpA and SdrC were higher in clinically cured SABP patients than in clinical failures. Anti‐LukAB NAb levels were elevated in all cohorts. Increased odds of cure correlated with higher haemolytic activity of SA strains, longer time between surgery and bacteremia (> 30 days), longer duration of antibiotic therapy, lower acute physiology and total APACHE II scores, lack of persistent fever for > 72 h and higher levels of antibodies against AT (IgG), ClfA (IgM), FnbpA (IgM) and SdrC (IgM). Discussion: Limitations included the cross‐sectional observational nature of the study, small sample size and inability to measure antibody levels against all SA virulence factors. Conclusion: Our results suggest that SABP patients may benefit from immunotherapy targeting multiple SA antigens. Abstract : Increased odds of cure in Staphylococcus aureus bacteremic pneumonia patients correlated with higher haemolytic activity of S. aureus strains, longer time between surgery and bacteremia (> 30 days), longer duration of antibiotic therapy, lower acute physiology and total APACHE II scores, lack of persistent fever for > 72 h and higher levels of antibodies against AT (IgG), ClfA (IgM), FnbpA (IgM) and SdrC (IgM).